THE RESTAURANT AT THE END OF THE METAVERSE. - BALL, JAMES (Prospect)
The article examines the failure of Meta’s Horizon Worlds, a virtual reality (VR) metaverse project heavily funded by Mark Zuckerberg’s company, Meta, which invested over $80 billion before scaling back its VR ambitions in 2026. Despite promises of a persistent, interconnected digital world with user-generated content and commercial opportunities, Horizon Worlds struggled with low user engagement and technical limitations, reflecting broader historical challenges in VR adoption. The piece situates this failure within the long-standing vision of the metaverse and VR, noting that major tech companies are now shifting focus toward artificial intelligence instead. It highlights the disconnect between tech industry ambitions and public interest, emphasizing that consumers have ultimately rejected this vision of the future.